1999
DOI: 10.1006/jmla.1999.2635
|View full text |Cite
|
Sign up to set email alerts
|

Facilitatory Effects of Vowel Epenthesis on Word Processing in Dutch

Abstract: We report a series of experiments examining the effects on word processing of insertion of an optional epenthetic vowel in word-final consonant clusters in Dutch. Such epenthesis turns film, for instance, into filəm. In a word-reversal task listeners treated words with and without epenthesis alike, as monosyllables, suggesting that the variant forms both activate the same canonical representation, that of a monosyllabic word without epenthesis. In both lexical decision and word spotting, response times to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Van Donselaar, Kuijpers, and Cutler (1999) found that recognition of variant words produced with an optional vowel (vowel epenthesis) was faster than the canonical, schwa-less, pronunciations. Van Donselaar et al suggest that the inclusion of the schwa enhanced perceptibility of the cluster's initial consonant.This could accommodate the present f inding that recognition of deleted tokens was more difficult.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Van Donselaar, Kuijpers, and Cutler (1999) found that recognition of variant words produced with an optional vowel (vowel epenthesis) was faster than the canonical, schwa-less, pronunciations. Van Donselaar et al suggest that the inclusion of the schwa enhanced perceptibility of the cluster's initial consonant.This could accommodate the present f inding that recognition of deleted tokens was more difficult.…”
Section: Discussionmentioning
confidence: 97%
“…As our and other recent data make clear, however, this is not always the case. We have discussed two of these studies above (i.e., Utman et al, 2000;van Donselaar et al, 1999). Since there is no longer a ubiquitous advantage to repetition cases per se, the current state of research simply does not permit a clear statement concerning the benefit of repetition, relative to other priming conditions.Clearly, additionalresearch is required to place theoretical constraints on the locus of repetition priming effects.…”
Section: Discussionmentioning
confidence: 99%
“…the realization of intervocalic stops in American English as flaps; Connine, 2004;McLennan et al, 2003), reduction (the deletion of single or multiple segments from words; Ernestus et al, 2002;LoCasto and Connine, 2002;Mitterer and Ernestus, 2006;Utman et al, 2000), and epenthesis (e.g. the insertion of the vowel schwa into the canonical form of a Dutch word; Donselaar et al, 1999). Space restrictions prevent detailed discussion of these phenomena.…”
Section: Which?mentioning
confidence: 99%
“…It is worth noting, however, that, as with assimilation, word recognition in the context of such processes entails a combination of phonological knowledge (e.g. knowledge about where epenthesis is legal; Donselaar et al, 1999), and the use of fine-grained phonetic detail to help recover the speaker's intentions (e.g. in the resolution of ambiguities between dernier oignon 'last onion' (with liaison) and dernier rognon 'last kidney' (without liaison); Spinelli et al, 2003).…”
Section: Which?mentioning
confidence: 99%
“…In line with this, the deletion of vowels, even where it occurs regularly in casual speech, makes words harder to recognize: for example, lexical decision responses can be slower for words with deleted vowels ͑e.g., s'maine for semaine; Racine and Grosjean, 2000͒. In contrast, insertion of a vowel into a consonant cluster ͑e.g., fillum for film͒ makes recognition easier, in part because the consonants in the cluster indeed become easier to identify if separated ͑van Donselaar et al, 1999͒. Vowel devoicing in Japanese could thus be perceptually disadvantageous. Further, it could complicate the parsing of continuous speech into its component words.…”
Section: Introductionmentioning
confidence: 99%